Pengaruh Kunyit dalam Pengelolaan Stres Oksidatif dan Implikasinya terhadap TNF Alfa dan Kesehatan Sel - Made Rendra Wisnu Rahasbistara (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article aims to examine the relationship between turmeric consumption and the management of oxidative stress and its effects on TNF-α expression and cellular health, in order to provide a scientific understanding of turmeric's potential as a therapeutic agent in the prevention and treatment of various degenerative diseases through antioxidant and anti-inflammatory mechanisms. This study uses a qualitative approach with a literature review method to examine the effect of turmeric, specifically curcumin, in managing oxidative stress and TNF-α expression related to cellular health. Data were collected through a search of scientific literature from trusted sources such as PubMed, Scopus, and Google Scholar, with a focus on relevant and credible publications. The analysis was conducted descriptively and analytically to synthesize new understanding of curcumin's role as a natural agent in cell protection and recovery. The results show that curcumin in turmeric has a positive impact on cellular health by increasing the body's antioxidant activity. Curcumin is also effective in reducing inflammation-causing compounds, thereby helping to relieve inflammatory symptoms. These effects accelerate cell regeneration, strengthen connective tissue, and accelerate wound healing. Thus, curcumin has great potential as a natural agent in the prevention and treatment of various disorders related to oxidative stress and chronic inflammation.